Using Facebook Ads to promote blood pressure checks among African Americans in the United States: A descriptive study - Katherine J POLAK; Jessica LC SAPP; Jennifer L SEDILLO (Journal of Health and Social Sciences)
Introduction: Although hypertension is common in the United States, the African American community is disproportionately affected by high blood pressure. The purpose of this study was to evaluate the use of Facebook ads and posts for an online health campaign to promote blood pressure checks among African Americans in the United States. Methods: The Measure Your Pressure (MYP) health campaign administered from May 2019 to August 2019 included Facebook advertisements, Facebook posts, and an online blog article. The Facebook adverti- sements included learn more ads, like page ads, and a web-based survey ad. These ads were delivered to two target audiences: 1) individuals at least 18 years old and located in the U.S., and 2) individuals at least 18 years old, located in the U.S., with special interest or behavior in African American culture, and multicultu- ral affinity: African American (US). A web-based survey was used to ask Facebook users’ opinions about the MYP Survey ad. To compare the ads between the general and interest groups, t-tests were used to analyze the reach, impressions, results, and cost per result. Results: There were 7 Facebook ads which reached 79,812 people. There were 121,683 impressions and 2,057 clicks. When comparing the ads between the general audience and interest groups, there was no si- gnificant difference for reach (P = 0.377), impressions (P = 0.427), results (P = 0.356), or cost per result (P = 0.484). There were 11 Facebook posts published which reached 2,171 users. Out of the 386 clicks received from the MYP Survey ad, there were only 11 that completed the web-based survey. Conclusion: This study shows that it may be possible to indirectly reach larger portions of at-risk indivi- duals with Facebook, but there is no significant difference between ad performance of target audiences using interest groups and general groups. Facebook does not make race demographics available to advertisers, so it is difficult to discern if the population of Facebook users reached were part of the African American community.